Dakwah Pemberdayaan: Studi Kasus Kegiatan Agribisnis di Pesantren Muhammadiyah Green School Wonogiri - Triatmo, Agus Wahyu; Husen, Fathurrohman; Amin, Juhdi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
Muhammadiyah Green School (MGS) Wonogiri is an environmentally sound pesantren. This pesantren places agriculture as part of the daily activities of the pesantren. This study aims to describe the da'wah of pesantren empowerment at MGS, focusing on its agribusiness activities. Data collection techniques used observation, in-depth interviews, and forum group discussions. The subjects studied were MGS Wonogiri stakeholders, ranging from leaders, assatiz, to santri. As a result, empowerment da'wah at MGS consists of two categories, namely education and training. Santri are motivated to become smart farmers after doing education. Santri and asatiz, actively practice horticultural farming activities, both planting, caring for and maintaining plants, to being involved in harvesting the results. The da'wah of empowerment collaborates with the Wonogiri Agriculture Office. Santri and asatiz are involved in the practice of processing the harvest, to make it as food for the internal needs of the pesantren residents themselves. As a result, pesantren can include agribusiness activities in the curriculum and extracurricular activities. Institutionally, pesantren can form an agribusiness activist organization as the person in charge of the extra program.